TIME-DEPENDENT BEHAVIOUR OF STEEL FIBRE REINFORCED CONCRETE ELEMENTS UNDER SUSTAINED AND REPEATED VARIABLE LOADS - Nakov, D. (MASE - Macedonian Association of Structural Engineers Faculty of Civil Engineering, ul. Partizanski odredi br. 24 P.Box. 560, 1000 Skopje, Republic of Macedonia, 2015)
Large experimental program was performed at the Faculty of Civil Engineering in Skopje to find out how steel fibres affects the time-dependent deformation properties of concrete and how does this influence reflects on the global behaviour of concrete elements in terms of time-dependent crack widths, deflections and strain distribution. Specific realistic loading with sustained and variable loads was applied on full scale steel fibre reinforced concrete beams that were monitored up to an age of concrete of 400 days. According to the experimentally obtained results, two advanced models for prediction of creep and shrinkage deformations were used: Fib Model Code 2010 and B3 model. Based on the analysis performed by AAEMM it was concluded that the factor psi2 depends linearly on the variable load duration and on the ratio of residual tensile strength to concrete compressive strength.
Keywords: Steel fibre reinforced concrete, long-term load, factor psi2